Penerapan Protokol Kesehatan Covid–19 Relawan Palang Merah Indonesia Pada Tanggap Darurat Bencana Gempa Bumi Sulawesi Barat - Nismawati Natsir; Marhtyni Natsir; Andi Auliyah Warsyidah (Jurnal Komunitas Kesehatan Masyarakat, 2021)
Indonesia is geographically located within the assemblage of three plates, namely Indo-Australia Plate, Eurasia Plate, and Pacific Plate. This plates assemblage causes Indonesia to be apotential place for natural disaster. An arthquake that recently took place in West Sulawesi haveresulted landslide and forced some districts to be isolated. In an attempt to establish a DisasterEmergency Response (DER) plan in West Sulawesi, the vital role of volunteer (e.g. TheIndonesian Red Cross) is extremely needed. However, the emergence of an earthquake duringthe pandemic have put the crisis mitigation in more complicated stance as both, society and thevolunteer, have to implement control measures in order to prevent the virus to spread morewidely. This study aims to provide an overview of COVID-19 health protocol implementation byThe Indonesian Red Cross (IRC) volunteer during disaster emergency response period in SouthSulawesi. Field observation with descriptive approach was applied as the main method. Thepopulation of this study was subjected to all Indonesian Red Cross Volunteer whose in chargeduring disaster emergency response period in South Sulawesi, and purposive sampling techniquewith some specific criteria such as; registered as Indonesian Red Cross volunteer proven bymembership card, have been serving for at least a week in DER location, and were in disasterlocation when the questionnaire were distributed, was chosen as our sampling method. Thefindings revealed that (1) 89% of the volunteers have clearly understood the risk of COVID-19, (2)58% of them have used the face mask correctly, (3) 73% of them have performed handwashingwith soap and water regularly, (4) 38% of them have implemented physical distancing in disasterlocation, while the rest 62% volunteers were reported otherwise.